2014
DOI: 10.1186/cc14002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest patients have an impaired immune response, which is not influenced by induced hypothermia

Abstract: IntroductionInduced hypothermia is increasingly applied as a therapeutic intervention in ICUs. One of the underlying mechanisms of the beneficial effects of hypothermia is proposed to be reduction of the inflammatory response. However, a fear of reducing the inflammatory response is an increased infection risk. Therefore, we studied the effect of induced hypothermia on immune response after cardiac arrest.MethodsA prospective observational cohort study in a mixed surgical-medical ICU. Patients admitted at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
9
28
1
Order By: Relevance
“…Our finding that HLA‐DR expression on monocytes decreased after ROSC is consistent with previous results . However, unlike in the previous reports, we did not find a significant difference in HLA‐DR expression on monocytes between survivors and non‐survivors on day 1.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our finding that HLA‐DR expression on monocytes decreased after ROSC is consistent with previous results . However, unlike in the previous reports, we did not find a significant difference in HLA‐DR expression on monocytes between survivors and non‐survivors on day 1.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that TNF‐α and IL‐6 levels decrease after whole blood stimulation with LPS, indicating the functional suppression of circulatory immune cells . The high rates of infections in patients with OHCA may be due to immune system suppression.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Post-arrest patients have a modest systemic inflammatory response compared to healthy controls, associated with lower HLA-DR expression and attenuated immune response to Gramnegative and Gram-positive antigens [23]. Inhibition of the exaggerated systemic inflammatory response syndrome is thought to be one of the mechanisms through which TTM can mitigate the harmful effects of ischemia-reperfusion.…”
Section: Inflammatory and Immune Responsementioning
confidence: 99%
“…Beurskens et al [23] conducted a cohort study to enlighten the impact of TTM on immune response after CA. They reported that CA patients maintained in mild hypothermia (at 36°C) had higher plasma cytokines levels than that of healthy controls, which was not apparent in patients kept at 33°C.…”
Section: Inflammatory and Immune Responsementioning
confidence: 99%